2024
DOI: 10.1186/s12872-024-03727-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals hub genes of myocardial infarction-associated endothelial cells

Hao Wang,
Liping Dou

Abstract: Background Myocardial infarction (MI) is a cardiovascular disease that seriously threatens human health. Dysangiogenesis of endothelial cells (ECs) primarily inhibits recovery from MI, but the specific mechanism remains to be further elucidated. Methods In this study, the single-cell RNA-sequencing data from both MI and Sham mice were analyzed by the Seurat Package (3.2.2). The number of ECs in MI and Sham groups were compared by PCA and tSNE algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Once the overall "trajectory" of gene expression changes is known, Monocle can place each cell in the appropriate position in the trajectory [ 53 ]. After determining the differentiation starting point of ADSCs, Monocle can simulate the differentiation time of each cell, find the heat map and distribution map of gene expression that gradually increases or decreases with the differentiation time, namely Beam analysis, and then obtain the determinant genes related to differentiation [ 54 ]. Beam analysis of neuronal marker genes and stem cell marker genes in this study showed the trend of gene expression during the differentiation of ADSCs into neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Once the overall "trajectory" of gene expression changes is known, Monocle can place each cell in the appropriate position in the trajectory [ 53 ]. After determining the differentiation starting point of ADSCs, Monocle can simulate the differentiation time of each cell, find the heat map and distribution map of gene expression that gradually increases or decreases with the differentiation time, namely Beam analysis, and then obtain the determinant genes related to differentiation [ 54 ]. Beam analysis of neuronal marker genes and stem cell marker genes in this study showed the trend of gene expression during the differentiation of ADSCs into neurons.…”
Section: Discussionmentioning
confidence: 99%